Manipulation of chemically mediated interactions in agricultural soils to enhance the control of crop pests and to improve crop yield - Hiltpold, Ivan; Turlings, Ted (My University, 2012)
In most agro-ecosystems the organisms that feed on plant roots have an important impact on crop yield and can impose tremendous costs to farmers. Similar to aboveground pests, they rely on a broad range of chemical cues to locate their host plant. In their turn, plants have co-evolved a large arsenal of direct and indirect defense to face these attacks. For instance, insect herbivory induces the synthesis and release of specific volatile compounds in plants. These volatiles have been shown to be highly attractive to natural enemies of the herbivores, such as parasitoids, predators, or entomopathogenic nematodes. So far few of the key compounds mediating these so-called tritrophic interactions have been identified and only few genes and biochemical pathways responsible for the production of the emitted volatiles have been elucidated and described. Roots also exude chemicals that directly impact belowground herbivores by altering their behavior or development. Many of these compounds remain unknown, but the identification of, for instance, a key compound that triggers nematode egg hatching to some plant parasitic nematodes has great potential for application in crop protection. These advances in understanding the chemical emissions and their role in ecological signaling open novel ways to manipulate plant exudates in order to enhance their natural defense properties. The potential of this approach is discussed, and we identify several gaps in our knowledge and steps that need to be taken to arrive at ecologically sound strategies for belowground pest management.
Keywords: rhizosphere food web; root pest control; soil signaling; root volatile; crop protection; belowground plant defense; nematode; corn-rootworm larvae; nematode meloidogyne-incognita; herbivore-induced volatiles; plant-parasitic nematodes; below-ground herbivory; carbon-dioxide; entomopathogenic nematodes; host location; mating disruption; cyst nematodes